2006
DOI: 10.1016/j.jviromet.2006.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Importance of virus–medium interactions on the biological activity of wild-type Heliothine nucleopolyhedroviruses propagated via suspension insect cell cultures

Abstract: In vitro serial passaging of nucleopolyhedroviruses often results in virus instability, leading to reduction of both yield and biological activity of polyhedra (virus occlusion bodies). In this study, uncloned Helicoverpa armigera single-nucleocapsid nucleopolyhedrovirus (HaSNPV) and cloned Helicoverpa zea single-nucleocapsid nucleopolyhedrovirus (HzSNPV) were each serially passaged five times in both low cost (VPM) and commercial (Excell 401) media using H. zea cell cultures. When the experimental data was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Studies on Group I CfMNPV in CF‐2C1 cells57 and BmNPV in Bm5 cells55 did not follow BV production, but the modest cell growth reported after application of a low MOI (0.1 PFU per cell) was similar to that reported for AcMNPV at the same MOI,5 which suggested similarly fast infection kinetics. Studies on Group II SfMNPV in Sf9 cells58 also did not monitor BV production, but the infection kinetics appeared to be poor because the application of high MOIs (by adding 10% v/v of virus inoculum) still resulted in a doubling in cell density postinfection, similar to the experience with HaSNPV 20, 48…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies on Group I CfMNPV in CF‐2C1 cells57 and BmNPV in Bm5 cells55 did not follow BV production, but the modest cell growth reported after application of a low MOI (0.1 PFU per cell) was similar to that reported for AcMNPV at the same MOI,5 which suggested similarly fast infection kinetics. Studies on Group II SfMNPV in Sf9 cells58 also did not monitor BV production, but the infection kinetics appeared to be poor because the application of high MOIs (by adding 10% v/v of virus inoculum) still resulted in a doubling in cell density postinfection, similar to the experience with HaSNPV 20, 48…”
Section: Discussionmentioning
confidence: 91%
“…In this study, key cell‐specific infection kinetics were determined for suspension‐cultured wild‐type Helicoverpa armigera single‐capsid nucleopolyhedrovirus (HaSNPV) and its Few Polyhedra (FP) mutant, the first time for a Group II NPV. HaSNPV is a promising baculovirus biopesticide against the highly destructive and increasingly insecticide‐resistant Heliothine caterpillar pest complex1, 17 and is the subject of a decade‐long in vitro research program in this group 18–20…”
Section: Introductionmentioning
confidence: 99%
“…HaSNPV isolate AC53, also known as A44WT [10,16], was obtained from AgBiTech and isolate H25EA1 was selected in vitro by CSIRO from P9/H25WT [15,32,33,34,35], and obtained from the University of Queensland [17]. Both were originally isolated from cadavers of an unspecified Helicoverpa species in Queensland, Australia in 1973 and 1974, respectively, and passaged once through H. punctigera before repeated passage through H. armigera .…”
Section: Methodsmentioning
confidence: 99%
“…This protease, which is not present in the occlusion bodies produced in cell cultures, could be an additional factor of virulence, accelerating the dissolution of occlusion bodies in the insect midgut and thus contributing to increase its biological activity (Rohrmann, 2011). Finally, it has been also reported that the composition of the culture medium could affect the activity of occlusion bodies, but the causes are unknown (Pedrini et al, 2006).…”
Section: Product Yield and Qualitymentioning
confidence: 99%